2019
DOI: 10.1186/s12864-019-5911-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis of Phyllosticta citricarpa and Phyllosticta capitalensis, two fungi species that share the same host

Abstract: Background Citrus are among the most important crops in the world. However, there are many diseases that affect Citrus caused by different pathogens. Citrus also hosts many symbiotic microorganisms in a relationship that may be advantageous for both organisms. The fungi Phyllosticta citricarpa , responsible for citrus black spot, and Phyllosticta capitalensis , an endophytic species, are examples of closely related species with different behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…During preparing this manuscript, we noticed that a paper describing the genomic sequencing of P. citricarpa and P. capitalensis was published (Rodrigues et al, 2019). However, the general features of their genome sequences are of great difference from ours.…”
Section: Genome Assembly and General Featuresmentioning
confidence: 78%
“…During preparing this manuscript, we noticed that a paper describing the genomic sequencing of P. citricarpa and P. capitalensis was published (Rodrigues et al, 2019). However, the general features of their genome sequences are of great difference from ours.…”
Section: Genome Assembly and General Featuresmentioning
confidence: 78%
“…Differences in terms of pathogenesis-related proteins have been confirmed after the genome sequencing of the two species, disclosing a higher number of coding sequences in P. citricarpa (15,206 versus 14,797). Such a difference has been interpreted considering the presence of growth and developmental genes involved in the expression of pathogenicity [23].The issue of detection of contaminated material imported from areas where the pathogen is endemic has also prompted investigations concerning the assortment of Phyllosticta spp. able to colonize citrus plants in either symptomatic or latent courses.…”
mentioning
confidence: 99%
“…Differences in terms of pathogenesis-related proteins have been confirmed after the genome sequencing of the two species, disclosing a higher number of coding sequences in P. citricarpa (15,206 versus 14,797). Such a difference has been interpreted considering the presence of growth and developmental genes involved in the expression of pathogenicity [23].…”
mentioning
confidence: 99%
“…In that study, we found that the P. citricarpa genomic assembly consisted of 19,143 contigs with the N50 of 3049bp and the P. capitalensis genomic assembly contains 11,080 contigs with the N50 of 4925bp (Rodrigues et al, 2019). This means that their genome sequence was very fragmented and the incompleteness of the genome was also confirmed by their BUSCO analysis (Rodrigues et al, 2019). Thus, comparing with their genomic data, we believe that the data in this study is much better and more reliable.…”
Section: Resultsmentioning
confidence: 94%